Pendekatan Pastoral terhadap Pelestarian Hutan - David Eko Setiawan; Silas Dismas Mandowen (HUPERETES: Jurnal Teologi dan Pendidikan Kristen, 2021)
Forests are habitats for various species of living things. Their survival depends heavily on the preservation of their habitat. However, many forests have been damaged by human actions. It also poses a variety of ecological problems. This condition should encourage the church to find the right solution to the problem. Through the cultural mandate attached to it, the church is expected to play an active role in preserving forests. This can be realized through a pastoral approach oriented towards the involvement of the congregation in preserving forests from irresponsible actions. This research aims to show how important the role of the church in preserving forests. Through a concrete pastoral approach, the church can answer the cultural mandate.  The method used in this study is the literature method. The results of this study show that based on the principles of cultural mandate in the Bible, the church is required to be actively involved in addressing ecological problems. The involvement is manifested in the pastoral approach to the congregation by educating them about the nature of forests and through practical actions involving them to preserve forests as habitats for various species of living beings.  Hutan merupakan habitat bagi berbagai spesies mahkluk hidup. Kelangsungan hidup mereka sangat bergantung pada pelestarian habitatnya. Namun demikian banyak hutan yang telah rusak akibat ulah manusia. Hal itu rupanya juga menimbulkan berbagai problem ekologi. Kondisi ini seharusnya mendorong gereja untuk mencari solusi yang tepat atas masalah tersebut. Melalui mandat budaya yang melekat padanya, gereja diharapkan berperan aktif dalam melestarikan hutan. Ini dapat diwujudkan melalui pendekatan pastoral yang berorientasi kepada keterlibatan jemaat dalam melestarikan hutan dari tindakan yang tidak bertanggung jawab. Penelitian ini bertujuan untuk menunjukan betapa pentingnya peran gereja dalam melestarikan hutan. Melalui sebuah pendekatan pastoral yang konkrit, gereja dapat mengejawantahkan mandat budaya tersebut.  Adapun metode yang digunakan dalam penelitian ini adalah metode kepustakaan. Hasil dari penelitian ini menunjukkan bahwa berdasarkan prinsip-prinsip mandat budaya yang ada di dalam alkitab, gereja dituntut untuk terlibat aktif dalam mengatasi problem ekologi. Keterlibatan itu diwujudkan dalam pendekatan pastoral kepada jemaat dengan mengedukasi mereka tentang hakikat hutan serta melalui tindakan-tindakan praktis yang melibatkan mereka untuk melestarikan hutan sebagai habitat bagi berbagai spesias mahkluk hidup.